Bearing Witness: A Pacific Climate Crisis Documentary and Journalism Development Project. (June 2020) - Robie, David; Marbrook, Jim
A three-year Pacific climate research and storytelling documentary and journalism project has contributed to a disruption and renewal theme in Pacific Island Countries development. Focused initially on Fiji, the project has involved three pairs of postgraduate students engaging with climate crisis challenges. Responding originally to the devastation and tragedy wrought in Fiji by Severe Tropical Cyclone Winston in 2016, the Pacific Media Centre embarked on the Bearing Witness journalism project by sending two postgraduate students to Viti Levu to document and report on the impact of climate change (Robie & Chand, 2017). Their main component was a multimedia report on Daku village in the Rewa River delta area. This was followed in 2017 with a series of reports leading to a multimedia package on the relocation of the remote inland village of Tukuraki (Robie, 2018). The third episode focused far more strongly on documentary with reports on waka navigation and climate change, the 'ghost village' of Vunidogoloa and a 'homecoming' short feature about the Banaban people of Rabi and the impact on them caused by climate change. The project explores Friere's notions of 'critical consciousness' as they might relate to teaching documentary-making and also draw on the concept of talanoa journalism.